Implementing a Co-Teaching Model in Music Student Teaching: A Literature Review. (October 2019) - Kim, Jieun
The purpose of this literature review is to examine music education research concerning the emerging practice of co-teaching between cooperating music teachers and student teachers, and to understand the benefits of co-teaching for both. The review is organized into two sections: (a) how cooperating music teachers and student teachers view their co-teaching experiences and (b) how cooperating music teachers mentor student teachers in a co-teaching model. Co-teaching during student teaching can occur successfully through cooperating teachers' willingness to facilitate the co-teaching process, student teachers' reflective practice with cooperating teachers and careful sequencing in teaching opportunities, and co-teachers' engagement in daily communication activities. Music education researchers should continue to examine various topics related to implementing a co-teaching model in student teaching. This article will provide current P–12 music teachers with successful co-teaching examples and suggestions for applications in music classrooms.